The application of auto-poiesis to gender studies: the subject right to self-building in relation to his/her sexual identity - Vivanco Martínez, Ángela (Acta Bioethica, 2006)
This paper deals with some keys given by the gender studies in relation to the main roles of women and men and on the way Law adopts them. From this perspective, the critique of gender studies to the patriarchal model and it's ethical and legal questioning to a system of universal rights and to the constitutional concept of person is established. The last one stating a hierarchy for human beings and a dependency for stereotypes. On the contrary, a system of selfbuilding was postulated for the subject, which gathers the characteristics that Maturana and Varela gave to living beings, beyond seeing society as a closed unit. Consequently, the systematic use of conflict will be necessary for giving rise to "differences" and diverse and over- comprehensive status to human realities.